Kontribusi Layanan Penguasaan Konten dalam Meningkatkan Sikap Empati Siswa - Evi Fitriyanti; Solihatun Solihatun; Tanti Ardianti (Consilium : Berkala Kajian Konseling dan Ilmu Keagamaan, 2020)
This study aims to reveal how much the contribution of Content Satisfaction Services (PKO) in increasing students' empathy attitudes at SMK Taruna Bhakti Depok. This research uses a quantitative method with a descriptive correlational analysis approach that aims to find out how much influence between the research variables. This research variable consists of two, namely Content Mastery Service (PKO) (X) is an independent variable and Student Empathy Attitude (Y) is a dependent variable. Through PKO services provided to students in a classical format it is expected to help students have something useful to meet their needs and overcome the problems they face, especially in increasing students' empathy. The results showed that there was a contribution to the content mastery service (PKO) in significantly increasing students' empathy attitudes.